Perfect phrases for employee development plans : hundreds of ready-to-use phrases for motivating and growing employees for success - Bruce, Anne , 1952- (Perfect phrases series, 2010)
The secret to business success is employee and talent development. Companies that invest in branding and creating smart, 'upgradeable' talent are the ones that leads their industries in the future. This title includes hundreds of ready-to use phrases for ensuring your employees stay motivated and develop teamwork and sound work ethics